(untitled) (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the auditability and conflict-of-interest risks that arise from the establishment of Danantara under Law Number 1 of 2025 and Government Regulation Number 10 of 2025. The issue is legally significant because the 2025 amendment to the State-Owned Enterprises Law delegates part of the President’s authority in managing state-owned enterprises and separated state assets to a newly formed state-owned investment body. Using normative legal research with statutory and conceptual approaches, this article maps Danantara’s legal position, identifies the accountability pressure points generated by the transfer of authority, and formulates a minimum governance model centered on functional separation, auditable decision trails, and public responsibility. The analysis is grounded in verified primary legal sources and selected academic and governance literature relevant to Danantara’s institutional design.